Extranodal Biphenotypic Non-Hodgkin Lymphoma of the Popliteal Cavity: A Case Report and Review of Literature - Giulia A. Restivo; Lara Mussolin; Paolo D’Angelo; Angelica Zin; Martina Pigazzi; Elisa Carraro; Emanuele S. G. D’Amore; Marta Pillon; Piero Farruggia (Diagnostics, 2022)
Primary soft-tissue lymphoma (PSTL) is a rare extranodal non-Hodgkin lymphoma, characterized by a mass growing within soft-tissue, which is connective tissue, adipose tissue, and skeletal muscle. Here, we describe a case of biphenotypic lymphoblastic lymphoma arising from soft tissue of the popliteal fossa in an 11-year-old boy. A pediatric review about PSTL revealed that anaplastic large cell lymphoma is the most common histological type and a biphenotypic lymphoblastic lymphoma has not yet been reported in childhood. Lymphoma should always be considered in patients presenting with a soft-tissue mass, and a comprehensive immunohistochemical evaluation, including B-cell, T-cell, and myeloid markers, is needed to make a correct diagnosis and establish the most suitable treatment.